Bruxism in Children (Journal of Rangpur Medical College, 2024)
Background: Bruxism can occur in children living or residing in slums areas, rural areas, remote and urban communities. The prevalence of bruxism among children varies in the literature. Bruxism is associated with sound during teeth clenching or involuntary teeth grinding, and this can disturb parents, guardian and family members. It can be diagnosed with clinical history, clinical examinationand use of electromyography and polysomnography. Method: An electronic literature search in science direct and goggle was done in December 2023 using the Population, Concept and Context framework. Search terms and keywords were combined by Boolean operators. Two independent investigators screened titles and abstracts of publications on bruxism among children. Original (primary) research articles with accessible full text were included for review, while review articles, systematic reviews, thesis, dissertations and perspectives related to bruxism among children were among articles excluded during screening. Original (primary) research articles related to voluntary tooth clenching,other oral habits and bruxism/tooth grinding among children with special health care needs were also excludedduring screening. Results: Abstract and full texts were screened using inclusion criteria by two independent investigators. The identified study was carried out in Egypt, Ugandaand South Africa respectively. Conclusion: Bruxism can occur among children.Itcan affect the quality of life of childrenwith tooth sensitivity, tooth attrition with wear facets, and psychological concerns.More studies from diverse ethnic population and countriesin Africa countries will fill the gaps in knowledge and add to the existing literature.J Rang Med Col. March 2024; Vol. 9, No. 1: 82-85